Karateristik Sifat Kuantitatif dan Manajemen Pemeliharaan Ayam Cemani di Kelompok Tani Ternak Makukuhan Mandiri: Characteristics - Tatan Kostaman; Soni Sopiyana; Komarudin Komarudin (Jurnal Riset Agribisnis dan Peternakan, 2022)
The quantitative trait is a trait controlled by many genes and the differences between the phenotypes are not very clear and additive. The purpose of this study was to determine the characteristics of quantitative traits and maintenance management of Cemani chickens in the Makukuhan Mandiri farmers. The study was conducted in Temanggung Regency, using a purposive sampling method. The selected farmer were 13 respondents with the criteria of an experienced farmer, having good data, and track records in maintaining Cemani chickens. Primary data is obtained through direct observation and measurement in the field. Secondary data were collected by interview and questionnaire. Observed variables were respondent characteristics, population, management data, and quantitative characteristics. The data obtained were analyzed by calculating the mean value, standard deviation, and coefficient of variation. The results of quantitative trait measurements show that Cemani chicken is still pure. The Cemani chicken population based on age is very good, where there are more chicks compared to adult chicken. Meanwhile, the adult male and female ratio is 1: 5.38. Maintenance is carried out intensively. The Cemani chicken starter period is placed in the brooder cage. Grower period cages are 120 x 60 cm2 battery cages for 2-3 heads and the production period was in the form of a confined plot with a 6 x 4 m2 display containing 1 ♂ : 5 ♀. It can be concluded, the based on the quantitative trait of Cemani chickens in the Makukuhan Mandiri farmer shows the purity of Cemani chickens with a maintenance pattern using a ratio of 1 ♂ : 5 ♀.